Figure 2 from: Potapov G, Kondakov A, Kolosova Y, Tomilova A, Filippov B, Gofarov M, Bolotov I (2018) Widespread continental mtDNA lineages prevail in the bumblebee fauna of Iceland. ZooKeys 774: 141-153. https://doi.org/10.3897/zookeys.774.26466 - Potapov, Grigory S.; Kondakov, Alexander V.; Kolosova, Yulia S.; Tomilova, Alena A.; Filippov, Boris Yu.; Gofarov, Mikhail Yu.; Bolotov, Ivan N. (Zenodo, 2018)
Figure 2 Median-joining haplotype networks of the available COI sequences of bumblebee species inhabiting Iceland. The circle size is proportional to the number of available sequences belonging to a certain haplotype. The small red dots indicate hypothetical ancestral haplotypes. Red numbers near branches indicate the number of nucleotide substitutions between haplotypes. Black codes indicate the COI lineages inhabiting Iceland. A Bombus jonellus (N = 29) B B. lucorum (N = 115) C B. hortorum (N = 33). Photographs by Yulia S. Kolosova.